Analisis Pengaruh Faktor Spesifik Perusahaan terhadap Profitabilitas Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia Periode 2016 - 2021 - Asep Junjunan; Muhamad Umar Mai; Djoni Djatnika (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to determine the amount of the influence of the variables Operational Efficiency Ratio (BOPO), Financing to Deposit Ratio (FDR), Firm Size and Capital Adequacy Ratio (CAR) on Return on Asset (ROA) at Rural Bank Sharia (BPRS) in Indonesia. The population used is BPRS registered with the Otoritas Jasa Keuangan (OJK). The data used is secondary data derived from financial reports issued by OJK for the 2016-2021 period. The research method used is quantitative research with panel data regression analysis. The sample used in this study was 51 BPRS. The findings of this study are to provide contribution to BPRS regarding specific factors affecting the ROA of BPRS in Indonesian; and can be used as a reference and consideration for interested parties.